Determinants Of Business Success: An Analysis Of Islamic Perspective - Abdulkadir, Abubakar; Ibrahim, Muhammad Muslim (ADPEBI, 2022)
There exists misconception among some Muslims on the relationship between Allah’s decree and the success factors in human endeavors which business is one of them. In other word, what determined success in business is seen by many Muslims as just something that does not relate to human’s effort. This paper being conceptual tries to examine the relationship between the concepts –Allah’s decree, human’s effort and business success- as well as how Allah’s decree and then the human effort influence the determination of an individual future and the level of his achievement in business. The paper concludes that though Muslim has to believe in predestine but he has to also believe that Allah has tradition that obliged people to hold a curse, also it is part of the Allah’ s decree that made him to behave toward success or unsuccessful. The study recommends that that people should not only wish but also work toward success, therefore, success factors should be identified and effort should be made toward success and that individual and business should do their own part and leave the rest with Allah, this is where success lies.